COURSE PECULIARITIES OF NEUROCUTANEOUS MELANOSIS IN CHILDREN - Tatyana M. Prygunova; Ekaterina I. Кarpovich; Marina N. Chernigina; Elena E. Beresneva; Larisa A. Trynkova ("Paediatrician" Publishers LLC, 2016)
Neurocutaneous melanosis is part of a group of hereditary diseases characterized by large and/or multiple pigmented nevi, melanosis or melanoma of the pia mater, with no evidence of malignant skin lesions and involvement of other organs. The disease was described over 150 years ago, but its pathogenesis has not been studied yet, and treatment methods have not been developed yet. Different disease courses due to the pronounced polymorphism of clinical symptoms complicate the diagnosis, and the low efficacy of the symptomatic treatment worsens the disease prognosis. The article describes the experience of managing children with phakomatoses not similar to each other neither in debut and course nor in response to the therapy and prognosis. Early diagnosis of neurocutaneous melanosis in children allows to carry out timely symptomatic treatment and dynamical monitoring, and to improve the survival of patients.